2017
DOI: 10.2308/ogna-51849
|View full text |Cite
|
Sign up to set email alerts
|

Management of Financial Performance Measures: Evidence from Private Colleges and Universities

Abstract: This study examines the incentives for private colleges and universities (PCUs) related to financial reporting choices for net appreciation on endowments. Under current accounting standards, in the absence of explicit donor restrictions, PCUs are permitted to classify net appreciation as either unrestricted, which increases measures of operating performance, or as restricted, which constrains future actions but may also improve perceptions of various stakeholders. We analyze incentives related to four stakehol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The most common argument in favor of the change was that it followed UPMIFA, supplying information to assess an entity's liquidity constraints. As shown in Table 3, Panel A, there is an equal split among NFP colleges and universities on the proposal, which is not surprising since these organizations usually have significant discretion over accounting for endowments to fund scholarships, endowed faculty positions, and research activities (Burgstahler and Sawers 2017).…”
Section: Analysis Of Responses To Questions On Each Financial Statemementioning
confidence: 98%
See 4 more Smart Citations
“…The most common argument in favor of the change was that it followed UPMIFA, supplying information to assess an entity's liquidity constraints. As shown in Table 3, Panel A, there is an equal split among NFP colleges and universities on the proposal, which is not surprising since these organizations usually have significant discretion over accounting for endowments to fund scholarships, endowed faculty positions, and research activities (Burgstahler and Sawers 2017).…”
Section: Analysis Of Responses To Questions On Each Financial Statemementioning
confidence: 98%
“…Prior research has shown that managers of NFP organizations have a variety of incentives available to them related to performance evaluation, compensation, career advancement, and reputation. The extant literature indicates that these incentives can influence NFP managers' choices over accounting policies affecting financial measures, cost allocations, and resource allocations (Burgstahler and Sawers 2017).…”
Section: Background the Nfp Sectormentioning
confidence: 99%
See 3 more Smart Citations